2012
DOI: 10.1111/cbdd.12056
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of a Phenyl‐Amidine Class of NMDA Receptor Antagonists and the Rational Design of New Triazolyl‐Amidine Derivatives

Abstract: Recently, many efforts have been made to develop N-methyl-D-aspartic acid receptor antagonists for treating different pathological conditions such as thrombo-embolic stroke, traumatic head injury, Huntington's, Parkinson's, and Alzheimer's diseases). However, as side-effects limit the use of most antagonists, new drugs are still required. In this work, we performed a (quantitative) structure-activity relationship analysis of 17 phenyl-amidine derivatives (1a-1q), reported as N-methyl-D-aspartic acid receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Since glycine has been identified as a coagonist of NMDA, there has been a wide search for finding novel antagonists that could block the glycine binding NR1 subunit of NMDA receptor. 50 Molecular docking studies have found ifenprodil and similar compounds as novel blockers of the NR2B unit of NMDA. 51,52 Novel targets in AD…”
Section: N-methyl-d-aspartate Receptormentioning
confidence: 99%
“…Since glycine has been identified as a coagonist of NMDA, there has been a wide search for finding novel antagonists that could block the glycine binding NR1 subunit of NMDA receptor. 50 Molecular docking studies have found ifenprodil and similar compounds as novel blockers of the NR2B unit of NMDA. 51,52 Novel targets in AD…”
Section: N-methyl-d-aspartate Receptormentioning
confidence: 99%